1985
DOI: 10.1002/bit.260270323
|View full text |Cite
|
Sign up to set email alerts
|

Gas holdup and overall volumetric oxygen transfer coefficient in airlift contactors

Abstract: The two major types of airlift contactors, concentric-tube and external-loop, were investigated for their gas holdup (riser and downcomer) and overall mass transfer characteristics. Results obtained in batch charges of tap water and 0.15 kmol/m(3) NaCl solution are reported for external-loop airlift contactors having downcomer-to-riser cross-sectional area ratios, A(d)/A(r), ranging from 0.11 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
47
2
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(66 citation statements)
references
References 21 publications
14
47
2
3
Order By: Relevance
“…Consequently, the differences observed between the experimental values from this study and the values obtained from different theoretical correlations proposed by others [5,20,28] (Fig. 3b), are due to the fact that not all the parameters included in the current bioreactor design have their values within the range of the parameters for those proposed correlations (Ug, for example).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Consequently, the differences observed between the experimental values from this study and the values obtained from different theoretical correlations proposed by others [5,20,28] (Fig. 3b), are due to the fact that not all the parameters included in the current bioreactor design have their values within the range of the parameters for those proposed correlations (Ug, for example).…”
Section: Discussioncontrasting
confidence: 68%
“…A correlation for the kLa can be obtained as a function of the superficial gas velocity {kLa=α[1+Ad/Ar] -2 (Ug) ß } [20], such as the one presented in Fig. 6b, where the parameters α and β were adjusted using the experimental data, producing the following equation:…”
Section: Volumetric Oxygen Transfer Coefficientmentioning
confidence: 99%
“…This number is twice the increase reported by Bello et al (1985) (using a perforated plate) reflecting the formation of small bubbles by the membrane sparger-a characteristic which is less obvious in the coalescent liquid. In spite of this, our values for the coalescent liquid (coarse bubbles) are high compared with other systems (Bello et al, 1985;Heijnen and van't Riet, 1984). In the homogeneous flow regime gas holdup depends linearly on gas velocity (Deckwer and Schumpe, 1993) and can be estimated from Eq.…”
Section: Comparison Of Measured and Estimated Gas Holdupmentioning
confidence: 54%
“…Burckhart and Deckwer (1976) found a power law correlation, k L a ‫ס‬ 1.5v s 0.78 (method: gassing-in/out N 2 , 78-L liquid volume), for a sintered plate sparger in NaCl solutions Table I). Bello et al (1985) found k L a values for a perforated plate (conventional rigid sparger) in a ''bubble coalescence-inhibiting system'' of 0.15 M NaCl (method: gassing-in/out N 2 , 30-L liquid volume) of only 40% to 50% of the values obtained in this report.…”
Section: Gas-liquid Mass Transfer Coefficient Measured By Dynamic Metmentioning
confidence: 66%
“…One Is based on empirical correlation (Bello et al 1985;Chlstl et al 1987;Gavrllescu and Tudose 1998;Popovic and Robinson 1984;Popovic and Robinson 1988) Zuber and Findlay (1965), which Is Independent of geometrical restrictions, but more efforts are needed on experimentally determining parameters. can reduca the gas holdup In the riser of airlift reactor.…”
Section: Prediction Equation Of Gas Holdup In the Riser (B)mentioning
confidence: 99%